Penguatan Minat Kunjungan Wisatawan dan Media Promosi melalui Media Sosial di Taman Wisata Sokosewu Sukorejo Ponorogo - Safrian, Fanny; Ansori, Teguh; Wathoni, Syamsul (Social Science Academic, 2025)
This article discusses the use of social media as an effective promotional tool in Sokosewu Park's modern marketing strategy. The main aim of this article is to explore how social media can be used to increase name visibility, expand audience reach, and encourage deeper interactions with Sokosewu Park tourists. The method used in this research is the Asset Based Community Development (ABCD) method which prioritizes the utilization of assets and potential that exist around Sokosewu Park and are owned by the community. To then be used as material that empowers Sokosewu Park and the community itself. The research results show that strategic use of social media can significantly increase audience reach and tourist engagement. An integrated campaign with high-quality content and the right platform selection results in a significant increase in tourist destination recognition and tourist response. These findings confirm that social media, when used appropriately, is a powerful promotional tool that can support marketing objectives and strengthen relationships with target audiences.